MXene catalytic amplification-fluorescence/absorption dimode aptamer sensor for the detection of trace Pb2+ in milk - Zhi, Shengfu; Wei, Qi; Zhang, Chi; Yi, Chenguang; Li, Chongning; Jiang, Zhiliang (Frontiers in Nutrition, 2022)
Lead ion (Pb2+) is a toxic heavy metal, which is very harmful to organisms. Therefore, the establishment of a rapid, simple and sensitive method is of great significance for food safety and human health. It was found that MXeneTi3C2 nanosheet had a strong catalytic effect on the oxidation of 3,3,5,5-tetramethylbenzidine (TMB) via H2O2 to form the oxidized product (TMBOX), it has a strong fluorescence peak at 415 nm and an absorption peak at 295 nm. Aptamer of Pb2+ (Aptpb) can be adsorbed on the surface of nanosheet to form MXene-Apt conjugates, which reduces its catalytic active sites and inhibits its catalytic activity. When the target Pb2+ is added, it specifically binds with Aptpb to releases MXene nanosheets to enhance the dimode signals. Therefore, a new MXene catalytic fluorescence/absorption dimode aptamer biosenering platform was fabricated for the determination of trace Pb2+ in milk and water samples, with a fluorescence assay linear range of 5.0×10-2~2.0 nmol/L.